From Disaster Solidarity to "Multicultural Conviviality". Risks and Opportunities for Migrants in Japan after the Great Hanshin Earthquake - Peruzzi Castellani, Beniamino (PARTECIPAZIONE E CONFLITTO, 2023)
This paper is aimed at contributing to the discussion about practices of solidarity in contexts of shrinking civic space by bringing the focus on Japan. The country is famous for its restrictive migration policies and obstruction of pro-migrant practices. There is, however, a specific societal dimension where solidarity-makers can find spaces and opportunities: that is, the prevention of, and reaction to, natural disasters. The paper is structured in four sections. First, I present an overview of the context and the consequences of the Great Hanshin Earthquake (1995), by focusing on the unprecedented rise of the civil society that followed the disaster. Then, I turn to consider the situation of the migrants living in the Hanshin area at the time of the earthquake, and how they have been at the center of many initiatives of Japanese volunteers and NGOs. In a third section, I argue that, contrary to what is usually predicted by disaster research, those practices of solidarity did not disappear with the end of the emergency, but were progressively institutionalized and reproduced. Finally, I discuss how disaster solidarity has become an engine for the Japanese approach to cultural diversity, that is tabunka kyōsei ("multicultural coexistence/conviviality").